Proposta de uma arquitetura para detecção de situações de interesse e ações proativas em processos de negócio - Flores, Matheus Friedhein (2021)
With the advancement of technology and the constant search of organizations to improve their organizational processes, aiming to maximize the use of resources, several organizations are investing in improvements in the flow of their internal processes. In general, all organizations have tasks that are performed by different employees, given their role. A set of tasks, conditions and events characterizes a process. Tasks are handled by different sectors and employees, with or without the help of management software, characterizing process activities. This work proposes an architecture that seeks to detect situations of interest through process activities (events) in the business environment and initiate proactive actions in the face of these situations. For this, tools are used for processing event streams, such as: Apache Kafka and Apache Spark. In addition to the tools mentioned, for detecting situations of interest in business processes, the model proposed by Machado (MACHADO et al., 2017), has been extended to the business context. In order to evaluate the work, 02 (two) case studies were developed based on real scenarios worked throughout this dissertation. One in the research and development project entitled “Platform for Systems Integration based on mapping and process automation” and the other in the project entitled “Platform for Animal Health Defense of the State of Rio Grande do Sul (PDSA-RS)”. A prototype application was developed based on one of the scenarios.